Targeting gut microbiota and immune crosstalk: potential mechanisms of natural products in the treatment of atherosclerosis - Jing, Jinpeng; Guo, Jing; Dai, Rui; Zhu, Chaojun; Zhang, Zhaohui (Frontiers in Pharmacology, 2023)
Atherosclerosis (AS) is a chronic inflammatory reaction that primarily affects large and medium-sized arteries. It is a major cause of cardiovascular disease and peripheral arterial occlusive disease. The pathogenesis of AS involves specific structural and functional alterations in various populations of vascular cells at different stages of the disease. The immune response is involved throughout the entire developmental stage of AS, and targeting immune cells presents a promising avenue for its treatment. Over the past two decades, studies have shown that GM (GM) and its metabolites, such as trimethylamine-N-oxide, have a significant impact on the progression of AS. Interestingly, it has also been reported that there are complex mechanisms of action between GM and their metabolites, immune responses, and natural products that can have an impact on AS. GM and its metabolites regulate the functional expression of immune cells and have potential impacts on AS. Natural products have a wide range of health properties, and researchers are increasingly focusing on their role in AS. Now, there is compelling evidence that natural products provide an alternative approach to improving immune function in the AS microenvironment by modulating the GM. Natural product metabolites such as resveratrol, berberine, curcumin, and quercetin may improve the intestinal microenvironment by modulating the relative abundance of GM, which in turn influences the accumulation of GM metabolites. Natural products can delay the progression of AS by regulating the metabolism of GM, inhibiting the migration of monocytes and macrophages, promoting the polarization of the M2 phenotype of macrophages, down-regulating the level of inflammatory factors, regulating the balance of Treg/Th17, and inhibiting the formation of foam cells. Based on the above, we describe recent advances in the use of natural products that target GM and immune cells crosstalk to treat AS, which may bring some insights to guide the treatment of AS.